Bone mass, body composition and vitamin D status of ARV-naïve, urban, black South African women with HIV infection, stratified by CD(4) count - Hamill, M. M. (Springer London, 2013)
SUMMARY: This is the first report examining vitamin D status and bone mass in African women with HIV infection using dual-energy X-ray absorptiometry (DXA) with an appropriate HIV-negative control group. Unlike previous publications, it demonstrates no difference in bone mineral density (BMD) or vitamin D status in HIV-positive patients, at different disease stages, vs. HIV-negative subjects. INTRODUCTION: Low bone mass and poor vitamin D status have been reported among HIV-positive patients; suggesting HIV or its treatment may increase the risk of osteoporosis, a particular concern for women in countries with high HIV prevalence such as South Africa. We describe bone mass and vitamin D status in urban premenopausal South African women, who were HIV positive but not on antiretroviral therapy (ARV). METHODS: This study is a cross-sectional measurement of BMD and body composition by DXA and vitamin D status by serum 25-hydroxyvitamin D (25(OH)D) concentration. Subjects were recruited into three groups: HIV negative (n = 98) and HIV positive with preserved CD(4) cell count (non-ARV; n = 74) or low CD(4) cell counts prior to ARV initiation (pre-ARV; n = 75). RESULTS: The mean (standard deviation (SD)) age of women was 32.1 (7.2) years. Mean CD(4) (SD) counts (×10(6)/l) were 412 (91) and 161 (69) in non-ARV and pre-ARV groups (p < 0.0001). Pre-ARV women were significantly lighter and had lower mean BMI than the other two groups (p < 0.002). The pre-ARV group also had significantly less fat and lean mass compared with non-ARV and HIV-negative subjects (p ≤ 0.05). After full adjustment, there were no significant differences in BMD at any site (p > 0.05) between the groups, nor was vitamin D status significantly different between groups (p > 0.05); the mean (SD) cohort 25(OH)D being 60 (18) nmol/l. CONCLUSION: Contrary to previous studies, these HIV-positive women did not have lower BMD or 25(OH)D concentrations than HIV-negative controls, despite the pre-ARV group being lighter with lower BMI. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00198-013-2373-y) contains supplementary material, which is available to authorized users.